Is Nature 'natural'? Preliminary Notes For an Evironmental Ethics and its Implication for Design Practices - Mitha Budhyarto (Universitas Multimedia Nusantara, 2013)
Jurnal Rumpun Ilmu Sosial dan Humaniora